2019
DOI: 10.1016/j.jadohealth.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Physical Activity Interventions in Prevocational Adolescents: A Systematic Review and Meta-Analyses

Abstract: Literature detailing the effectiveness of school-based physical activity promotion interventions in prevocational adolescents was reviewed to identify effective intervention characteristics. Methods: The search strategy assessed studies against inclusion criteria study design, study population, school setting, language, and construct. The risk of bias of the included studies was assessed, and extractions were made of the physical activity (PA) level outcome measures and intervention characteristics regarding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 48 publications
5
46
0
3
Order By: Relevance
“…In order to increase the participation of children in PA in schools and to prevent obesity effectively, it is necessary to increase the active time in physical education courses, to diversify the content of the course, to reevaluate the teacher qualifications and the number of students, to examine the effectiveness of programs for recess, in-school activity, extracurricular activities and school teams. Some systematic studies conducted in this respect have shown that school-based interventions can be effective in preventing obesity and promoting PA [29][30][31]. On the other hand, there are also studies in which variables such as obesity, PA and sedentary behavior are measured and no significant development can be observed [23,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the participation of children in PA in schools and to prevent obesity effectively, it is necessary to increase the active time in physical education courses, to diversify the content of the course, to reevaluate the teacher qualifications and the number of students, to examine the effectiveness of programs for recess, in-school activity, extracurricular activities and school teams. Some systematic studies conducted in this respect have shown that school-based interventions can be effective in preventing obesity and promoting PA [29][30][31]. On the other hand, there are also studies in which variables such as obesity, PA and sedentary behavior are measured and no significant development can be observed [23,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Programs that promote children's and adolescents' PA are needed from an early age on [6]. The school setting provides the opportunity to implement appropriate programs [7], since every child and adolescent, independent of age and SES, is necessarily involved in activities embedded in the curriculum. Physical education (PE) teachers are well suited to motivate and educate children in adopting an active and healthy lifestyle, but how this support works in practice is in need of clearer definition in the context of PE.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have confirmed the effectiveness of PA promotion measures in school, university, and workplace settings [22][23][24][25][26], research is lacking about their effectiveness in the VET context. Notwithstanding, VET is a promising setting for PA promotion, as VET programs have a wide reach among adolescents and young adults, providing the opportunity to raise awareness of PA and health at an early stage of life [20,27].…”
Section: Introductionmentioning
confidence: 99%